2006
DOI: 10.2139/ssrn.946422
|View full text |Cite
|
Sign up to set email alerts
|

Technology Transfers and the Clean Development Mechanism in a North-South General Equilibrium Model

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Both the case studies (Forsyth, 1999, Duic et al, 2003, Forsyth, 2005, the partial equilibrium (Kemfert, 2003), the general equilibrium (Sahlén and Aronsson, 2006), and the strategic approaches (Matsuhashi et al, 1999, Millock, 2002 suggest that there is no one policy that addresses similarly the issues countries face, but rather, each country or partnership that collaborates in the CDM setting needs a specific solution to allow technology development and its transfer. Finally, an econometric study of the reported technology transfer by project types and countries suggests also a more microscopic analysis and understanding of the differences between determinants of technology transfer (Haites et al, 2006).…”
Section: Technology Transfer and Project Financingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the case studies (Forsyth, 1999, Duic et al, 2003, Forsyth, 2005, the partial equilibrium (Kemfert, 2003), the general equilibrium (Sahlén and Aronsson, 2006), and the strategic approaches (Matsuhashi et al, 1999, Millock, 2002 suggest that there is no one policy that addresses similarly the issues countries face, but rather, each country or partnership that collaborates in the CDM setting needs a specific solution to allow technology development and its transfer. Finally, an econometric study of the reported technology transfer by project types and countries suggests also a more microscopic analysis and understanding of the differences between determinants of technology transfer (Haites et al, 2006).…”
Section: Technology Transfer and Project Financingmentioning
confidence: 99%
“…Using a partial equilibrium model, Kemfert (2003) shows that trade barriers, would not only damage the economy, but could also deter investments in climate friendly technologies. Using a general equilibrium model, Sahlén and Aronsson (2006) add also labor barriers into the market of factors of production to account for north economies (capital intensive) and south economies (labor intensive). The effects of trade barriers (including labor) imply that for a CDM setting with allowed flows of factors of production -no borders, a technology transfer from the North to the South is clearly desirable from the perspective of a "global social planner," since the welfare gain for the South outweighs the welfare loss for the North.…”
Section: Technology Transfer and Project Financingmentioning
confidence: 99%
“…indirectly related to technology development, adjustment and transfer. Both the case studies (Forsyth, 1999;Duic et al, 2003;Forsyth, 2005;), the partial equilibrium (Kemfert, 2003), the general equilibrium (Sahlén and Aronsson, 2006), and the strategic approaches (Matsuhashi, Chang and Ishitani, 1999;Millock, 2002) suggest that there is no one policy that addresses similarly the issues countries face, but rather, each country or partnership that collaborates in the CDM setting needs a specific solution to allow technology and its transfer. Finally, an econometric study of the reported technology transfer by project types and countries suggests also a more microscopic analysis and understanding of the differences between determinants of technology transfer (Haites, Duan and Seres, 2006).…”
Section: Technology Transfer and Project Financingmentioning
confidence: 99%
“…Using a partial equilibrium model, Kemfert (2003) shows that trade barriers, would not only damage the economy, but could also deter investments in climate friendly technologies. Using a general equilibrium model, Sahlén and Aronsson (2006) add also labor barriers into the market of factors of production to account for north economies (capital intensive) and south economies (labor intensive).…”
Section: Technology Transfer and Project Financingmentioning
confidence: 99%